Hypertextualize the Back-and-Forth Verses - Iman Abbas Ghanem Al-Atabi; Aseel Miteb Al-Janabi (RES MILITARIS, 2023)
Textual interdependence is one way it is inferred from the harmony and coherence of texts, and it is a form of the miraculous statement of the heavenly book, similar to the tribal and remote interdependence of t. Commentators have insisted on resorting to the context to understand the ambiguous meanings in the Qur’anic verses, and interdependence is one of the means by which it is inferred from those texts. Saeed Yaqteen advocated for the term "textual attachment" to describe this connection between the two texts, which refers to how the word’s positive connotation is connected to the writing of a particular author or model. Saeed Yaqteen has continued to follow this writer’s lead by weaving or broadening his own experience. Because the Qur’an is a sacred text that is venerated by it and, on the other hand, is a miraculous book above all words, the interdependence is discussed within the text and not outside of it.